(Di)Simulation of the Bestiary Genre in Animalia exstinta by Esteban Seimandi, Hugo Horita, and Juan Cruz Bazterrica - Cruz, Ailén (Revista Canadiense de Estudios Hispánicos, 2021)
This article explores one of the latest branches in the evolution of the bestiary genre in contemporary Hispanic literature, (di)simulating bestiaries. The bestiary, a literary genre that proliferated during the medieval period, drew attention with its illustrations and illuminations, as well as the allegories it featured, fulfilling a didactic, Christian function. Although new Hispanic bestiaries published in the past two decades respect the form of the bestiary, that is to say, the presentation of the message with a title, image, and short text, they also offer increasingly creative interpretations that play with the content of the genre. This article explores a subcategory of bestiaries, which through their content pose as other genres for ludic literary purposes. The present study focuses on Animalia exstinta, written by Esteban Seimandi, illustrated by Hugo Horita, and designed by Juan Cruz Bazterrica. Using Jean Baudrillard’s concepts of simulacra and simulation, as well as surface and symptomatic reading, the article analyzes how Animalia exstinta simulates an environmental manifesto from fragments of contemporary Argentine culture and nostalgia.